2015
DOI: 10.1371/journal.pone.0132579
|View full text |Cite
|
Sign up to set email alerts
|

Targeting of Topoisomerase I for Prognoses and Therapeutics of Camptothecin-Resistant Ovarian Cancer

Abstract: DNA topoisomerase I (TOP1) levels of several human neoplasms are higher than those of normal tissues. TOP1 inhibitors are widely used in treating conventional therapy-resistant ovarian cancers. However, patients may develop resistance to TOP1 inhibitors, hampering chemotherapy success. In this study, we examined the mechanisms associated with the development of camptothecin (CPT) resistance in ovarian cancers and identified evodiamine (EVO), a natural product with TOP1 inhibiting activity that overcomes the re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
27
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(27 citation statements)
references
References 48 publications
0
27
0
Order By: Relevance
“…Camptothecin, the first small molecule targeting Top I for the treatment of advanced digestive carcinoma in clinical2331, which stabilizes the DNA cleavable complex to block the transient breaking and rejoining of DNA173233 and has been used as the Top I poison for the treatment of many digestive solid tumors widely34, was served as the positive control. As shown in Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Camptothecin, the first small molecule targeting Top I for the treatment of advanced digestive carcinoma in clinical2331, which stabilizes the DNA cleavable complex to block the transient breaking and rejoining of DNA173233 and has been used as the Top I poison for the treatment of many digestive solid tumors widely34, was served as the positive control. As shown in Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Numerous researches have reported that TOP1 is over-expression in various kinds of human tumors [38–41]. Increasing evidences demonstrate that TOP1 protein level, gene copy number, and mRNA expression are significantly correlated to unfavorable prognosis in most types of tumor [26, 42, 43]. However, the prognostic effect of TOP 1 in some tumors was controversial.…”
Section: Discussionmentioning
confidence: 99%
“…Camptothecin is a topoisomerase I inhibitor acting to induce DNA breaks. The cancer cells over‐expressed XRCC1 resist to camptothecin and the XRCC1 deficient cells are sensitive to camptothecin . Therefore, these data suggest XRCC1 would be an important target for BBR to function in DNA repair.…”
Section: Resultsmentioning
confidence: 86%
“…The cancer cells over-expressed XRCC1 resist to camptothecin and the XRCC1 deficient cells are sensitive to camptothecin. 35,36 Therefore, these data suggest XRCC1 would be an important target for BBR to function in DNA repair. We also tested the synergistic effects between BBR and HU, as well as between BBR and olaparib.…”
Section: Berberine Sensitizes Mda-mb-231 Cells To Cisplatin Camptomentioning
confidence: 84%